New small molecules in dermatology: for the autoimmunity, inflammation and beyond - Criado, Paulo Ricardo; Lorenzini, Daniel; Miot, Hélio Amante [UNESP]; Bueno-Filho, Roberto; Carneiro, Francisca Regina Oliveira; Ianhez, Mayra (Springer Nature, 2023)
Objective and design: The discovery of new inflammatory pathways and the mechanism of action of inflammatory, autoimmune, genetic, and neoplastic diseases led to the development of immunologically driven drugs. We aimed to perform a narrative review regarding the rising of a new class of drugs capable of blocking important and specific intracellular signals in the maintenance of these pathologies: the small molecules. Materials/methods: A total of 114 scientific papers were enrolled in this narrative review. Results: We describe in detail the families of protein kinases—Janus Kinase (JAK), Src kinase, Syk tyrosine kinase, Mitogen-Activated Protein Kinase (MAPK), and Bruton Tyrosine Kinase (BTK)—their physiologic function and new drugs that block these pathways of intracellular signaling. We also detail the involved cytokines and the main metabolic and clinical implications of these new medications in the field of dermatology. Conclusions: Despite having lower specificity compared to specific immunobiological therapies, these new drugs are effective in a wide variety of dermatological diseases, especially diseases that had few therapeutic options, such as psoriasis, psoriatic arthritis, atopic dermatitis, alopecia areata, and vitiligo.
Keywords: Atopic; Dermatitis; Janus kinases; Mitogen-activated protein kinase kinases; Src-family kinases; Syk Kinase